Investigating Teachers’ Challenges and Alternate Solutions in Teaching Lower Grade Students Using Content and Language Integrated Learning (CLIL) in Efata Learning Center Jambi - Rahmadhana, Sharah (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study explores the challenges faced by teachers in implementing Content and Language Integrated Learning (CLIL) for lower grade students at Efata Learning Center in Jambi. Moreover, it also identifies potential solutions to improve teaching effectiveness. CLIL, which combines subject content with English language instruction, presents unique difficulties when applied to young learners who are still developing both cognitive and linguistic skills. Using a qualitative research method, data were collected through interviews. The findings revealed several key challenges, including limited student vocabulary, students’ self-doubt, insufficient teaching materials adapted for CLIL, and teachers’ lack of formal training in CLIL methodology. Additionally, cultural and linguistic gaps between content and language learning further complicated instruction. However, teachers have adopted various alternate solutions such as scaffolding techniques, motivational supports, incorporating interactive activities, and collaborating with other teachers to enhance their teaching strategies. It concludes that while CLIL offers significant educational benefits, its success depends on teacher preparedness, contextual adaptation, and continuous support. It also offers practical implications specifically for the Indonesian educational context, informing policy makers and educators on effective strategies for the successful implementation of CLIL to enhance both language proficiency and subject mastery.